Prediction of Prophylactic Peptide Vaccine Candidates for Human Papillomavirus (HPV): Immunoinformatics and Reverse Vaccinology Approaches - Ismail, Mehreen; Sajid, Zureesha; Ali, Amjad; Wu, Xiaogang; Muhammad, Syed A.; Shaikh, Rehan Sadiq (Current Proteomics, 2021)
Background: Human Papillomavirus (HPV) is responsible for substantial morbidity and mortality worldwide. We predicted immunogenic promiscuous monovalent and polyvalent T-cell epitopes from the polyprotein of the Human Papillomavirus (HPV) using a range of bioinformatics tools and servers. Methods: We used immunoinformatics and reverse vaccinology-based approaches to design prophylactic peptides by antigenicity analysis, T-cell epitopes prediction, proteasomal and conservancy evaluation, host-pathogen protein interactions, and in silico binding affinity analysis. Results: We found two early proteins (E2 and E6) and two late proteins (L1 and L2) of HPV as potential vaccine candidates. Of these proteins (E2, E6, L1 & L2), 2-epitopes of each candidate protein for multiple alleles of MHC class I and II were found, bearing significant binding affinity (>-6.0 kcal/mole). These potential epitopes for CD4+ and CD8+ T-cells were also linked to design polyvalent construct using GPGPG linkers. Cholera toxin B and mycobacterial heparin-binding hemagglutinin adjuvant with a molecular weight of 12.5 and 18.5 kDa were used for epitopes of CD4+ and CD8+ T-cells, respectively. The molecular docking indicated the optimum binding affinity of HPV peptides with MHC molecules. This interaction showed that our predicted vaccine candidates are suitable to trigger the host immune system to prevent HPV infections. Conclusion: The predicted conserved T-cell epitopes would contribute to the imminent design of HPV vaccine candidates, which will be able to induce a broad range of immune-responses in a heterogeneous HLA population.
Keywords: HPV